(X+4)+(3x-7)=(x-2)+(3x+8)

Simple and best practice solution for (X+4)+(3x-7)=(x-2)+(3x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X+4)+(3x-7)=(x-2)+(3x+8) equation:



(X+4)+(3X-7)=(X-2)+(3X+8)
We move all terms to the left:
(X+4)+(3X-7)-((X-2)+(3X+8))=0
We get rid of parentheses
X+3X-((X-2)+(3X+8))+4-7=0
We calculate terms in parentheses: -((X-2)+(3X+8)), so:
(X-2)+(3X+8)
We get rid of parentheses
X+3X-2+8
We add all the numbers together, and all the variables
4X+6
Back to the equation:
-(4X+6)
We add all the numbers together, and all the variables
4X-(4X+6)-3=0
We get rid of parentheses
4X-4X-6-3=0
We add all the numbers together, and all the variables
-9!=0
There is no solution for this equation

You can always share this solution

See similar equations:

| 7x+x+8=56 | | x+2x+4x=?7x | | 7x^2+86x+399=0 | | (9?x)?(2?x)=7 | | 9?x?2?x=7 | | .3x+.5x(50-x)=18 | | 49x+2=0 | | -6x+-55=1 | | -6x+(-55)=1 | | -6x-20=70 | | 15x^2-46+16=0 | | (3a-2)(5a-4)=(3a-2) | | 2(-1)-9y=-25 | | n+5-1=-1 | | n+5?1=?1 | | 2(5c+2)-2c=3(2c=3)=7 | | 5^2x+5=12^x | | 5(2y-1)-4(y-3)=20 | | 1^x=5x+2 | | -3(4p-2)=2(p-1) | | 4(x-1)+4x-1=4 | | (w-7)(w-9)=0 | | 5(9-4x)=40 | | 3(5x-7)=4 | | 3u+1=u+8 | | 2u+8=4+u | | 16a-21=20a+3 | | 10^2x=75 | | 16=n3/4 | | 7-5m=3m-1 | | 67w–71w+40w=72 | | x-(1237.5+0.25(x-12000)=30000 |

Equations solver categories